Changes in zooplankton communities along a mercury contamination gradient in a coastal lagoon (Ria de Aveiro, Portugal) - Cardoso, Patrícia Gonçalves
The main objective of this paper was to evaluate the impact of mercury on the zooplankton communities' structure and functioning and their bioaccumulation patterns along a contamination gradient in a temperate coastal lagoon. Our results demonstrated that total abundance was not negatively affected by Hg contamination, since the most contaminated areas presented the highest values, being the copepod Acartia tonsa the dominant species, which means that it is a very well adapted and tolerant species to mercury. Nevertheless, negative effects were observed in terms of species diversity, since the most contaminated areas presented the lowest values of species richness, evenness and heterogeneity. Moreover, the spatial mercury gradient was reflected on the bioaccumulation patterns of the zooplankton communities. This reinforces the idea that zooplankton can be considered as an important vehicle of mercury transfer through the food pelagic web since it constitutes a primordial food resource for several commercial fish species.